Evaluation of Extreme Waves Associated with Cyclonic Activity on San Andrés Island in the Caribbean Sea since 1900 - Ortiz Royero, Juan Carlos (2015)
San Andrés Island is one of the most important tourist destinations in the Caribbean Sea. The extreme waves associated with storms and hurricanes since 1900 were studied. A total of 17 important events was identified in the last 100 years. During seven of these events, the eye of the storm was located less than 150 km from the coast: hurricanes Hattie (1961), Alma (1970), Irene (1971), Joan (1988), Cesar (1996), Katrina (1999), and, the most recent, Beta (2005). Most commonly, the storms approached from the SE; these storms affected the northern and southern portions of the island. Using the parametric hurricane wind model and simulating waves nearshore wave model, the wind and wave fields were modeled for the aforementioned hurricanes. The results showed that the western area of the island was unaffected by extreme waves, except for the waves caused by Beta in 2005, which were less than 2 m in height (on the 50-m isobath). However, the situation is different in the east. The wide insular shelf and coral reefs located along the northeastern coast act as a natural barrier dissipating the extreme waves so that most of the wave energy is dispersed before reaching the coastline. The southeastern coast is totally exposed to wave energy because of its narrow insular shelf and the limited presence of coral reefs. The maximum estimated significant heights were as much as 5 m on the 50-m isobath and occurred during Hurricane Joan (1988); the peak wave period was 12 seconds, and most of the hurricanes came from the SE. The present paper establishes a fundamental basis for implementing management plans during emergencies related to hurricanes, considering that the island has been affected by at least one hurricane every 10 years for the last 50 years.